A multifunctional wearable E-textile via integrated nanowire-coated fabrics. Issue 25 (6th May 2020) - Lian, Yunlu; Yu, He; Wang, Mingyuan; Yang, Xiaonan; Li, Zhe; Yang, Fan; Wang, Yang; Tai, Huiling; Liao, Yulong; Wu, Jieyun; Wang, Xiangru; Jiang, Yadong; et al.
Abstract : We demonstrate a novel multifunctional E-textile which functions as a pressure sensor, Joule heater, thermal insulator, and PM2.5 filter. Abstract : Textile-based wearable devices have attracted increasing attention because of their softness, breathability, and biocompatibility, which makes them durable and wearable for long-term application. To date, the fabrication of multifunctional wearable electronic textiles (E-textiles) that integrate sensing and heating properties via an energy-saving method remains a great challenge. Herein, we have proposed a multifunctional integration strategy using integrated nanowire-coated fabrics that can deliver pressure sensing capabilities simultaneously with thermal insulation, Joule heating, and particulate matter (PM) filter features. The collective effect of the fiber/yarn/fabric multi-scale contacts produces a highly sensitive multifunctional E-textile, with a sensitivity of approximately 3.24 × 10 5 kPa −1 at 0–10 kPa and 2.16 × 10 4 kPa −1 at 10–100 kPa, respectively. Each layer contained a conductive network of metallic nanowires (NWs) that could reflect the infrared radiation (IR) emitted by the human body and synergistically enhance the thermal insulation property of the multifunctional E-textile, thus enabling a 5 °C decrease in the setpoint as compared to the normal cotton textile. In addition to passively insulating heat loss, the E-textile can also function as a wearable heater, inducing fast thermal response and uniform electroheating. Furthermore, it can act as a high-efficiency air filter for high-temperature PM2.5 particle removal. The outstanding integrated property is expected to be applicable in the fields of smart clothes, human monitoring and healthcare, air filtration, and lightweight body armor in extreme climate conditions.